The normativity of multiple social identity: from motivation to legitimacy - Shevchenko, Z. V.; Fialko, N. A. (Anthropological Measurements of Philosophical Research, 2022)
Purpose. The authors of this article aim to reveal how motivation and legitimacy ensure the normativity of the structuring and genesis of multiple social identity. Theoretical basis. Social constructivism was chosen as a research methodology. It reveals social identity as an identity constructed by its bearer on the basis of ready-made versions of social identity proposed by social groups and society. Social circles, identified by Georg Simmel, unite representatives of different social groups into a wider oneness, which can be interpreted as a multiple social identity, and the motivation for its formation can be identified on the basis of Weber’s concept of legitimacy. Originality. Identifying the structure and genesis of a multiple social identity creates prerequisites for establishing its normative foundations, as well as for a specific analysis of the procedures for achieving its motivation and legitimacy. Georg Simmel’s concept of social virtues promotes consideration of the basic virtues of an individual as those that enable one’s to be a member of various social groups in which these virtues are manifested. Conclusions. The social virtues present in the social identities that are part of a multiple social identity determine not only the social status of these individuals in these social groups but also the ranking and normative significance of these groups for this individual. If the observance of virtues in a certain social group causes a higher motivation of an individual’s behavior, then this group acquires a higher legitimacy for her/him. Using the example of virtues, it is possible to search for other possible grounds for the formation of multiple social identity. Such grounds are primarily other characteristics of key social practices that support different social groups.